Substitusi Tepung Tulang Ikan Tongkol pada Produk Nugget Tempe sebagai Makanan Alternatif Kaya Protein dan Kalsium untuk Balita: Substitution of Tongkol Fish Bone Meal in Tempeh Nugget Products as an Alternative Food Rich in Protein and Calcium for Toddlers - Utami, Dhita Camila; Sofyaningsih, Mira; Maulida, Nursyifa Rahma (Universitas Airlangga, 2025)
Background: One approach to preventing stunting is the provision of supplemental feeding (PMT). Tongkol fish bones are an underutilized waste product. An innovation in utilizing fish bone waste involves processing it into flour for inclusion in tempeh nugget formulations. Objectives: This study aims to develop a protein- and calcium-rich food source to support stunting prevention efforts among toddlers. Methods: This study employed an experimental design with quantitative analysis. A completely randomized design (CRD) was used with four factorial treatments and two replications. The ratios of Tongkol fish bone meal to wheat flour were 0:20 g, 5:15 g, 7:13 g, and 9:11 g. Chemical analysis was conducted to evaluate the nutritional content of tempeh nuggets, while organoleptic testing was employed to identify the optimal tempeh nugget formulation. Results: The selected formulation (F1, 25%) provided 84.8 kcal energy, 6 g protein, 4.15 g fat, 7.66 g carbohydrates, and 638.66 mg calcium per 100 g. A serving size of 7 pieces (50 g) contained 129 kcal energy, 6 g protein, 6 g fat, 11 g carbohydrates, and 292 mg calcium. Conclusions: Tempeh nuggets enriched with fish bone flour can be considered a viable source of protein and calcium, meeting nutritional claim thresholds.